The Effect of Problem-Based Spot Capturing Models on Creative and Care Character of Students in Elementary School - Ariesta, Freddy Widya (Journal of Education Reseach and Evaluation, 2018)
This study aims to determine the impact of applying problem-based spot capturing models in teaching social science in order to develop creativity and caring of students in elementary school. The experimental research was carried out for four weeks by using problem-based spot capturing models learning in two groups is experimental group (n = 24) and control group (n = 23). This study used quasi experimental method with pre-test and post-test control group design. The research instrument was taken from observation and questionnaire then the data was analysed by using qualitative descriptive percentage. Based on the data, the researchers figure out that a teacher plays an important role in developing the character of the students through the learning design. In addition, there are differences in the higher score obtained by the experimental group than the control group on creative and care characters by using problem-based spot capturing models. Students also gain an improvement in technology use and skills in social science class by using the problem-based spot capturing models.